Management Information System (MIS) for Achieving Work Efficiency and Effectiveness in Maximizing Employee Performance: A Conceptual Study as a Guide for Researchers - Gupron, Gupron; Yandi, Andri; Suprapto, Eko; Sadewa, Ifan (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
Management Information Systems (MIS) play a strategic role in enhancing the efficiency and effectiveness of an organization's operations. The implementation of MIS enables more structured data and information management, thereby supporting more accurate and faster decision-making. This study aims to analyze the concept and benefits of MIS in improving efficiency and effectiveness to achieve optimal work outcomes. The research method employed is a literature review, examining various references related to MIS implementation in different organizations. The findings indicate that a well-designed MIS can enhance both efficiency and effectiveness within an organization, ultimately contributing to optimal work performance. Additionally, MIS plays a crucial role in improving interdepartmental coordination and ensuring the optimal utilization of resources. These findings are expected to serve as a guide for researchers in understanding the role of MIS in modern management and provide valuable insights for organizations in optimizing the use of information technology.